2021
DOI: 10.33448/rsd-v10i6.13410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of packaging on the conservation of quality attributes of lamb’s-ear leaves during storage

Abstract: The objective of this study was to evaluate the influence of the packaging system on the useful life and post-harvest quality of lamb’s-ear leaves (Stachys byzantina L.). The sanitized sheets were packaged in four different packaging systems: (A) rigid polyethylene (PET), (B) PET together with ethylene-absorbing sachet, (C) PET wrapped with high barrier plastic film, and (D) PET together with an ethylene-absorbing sachet and wrapped with high barrier plastic film and stored at 7 ° C. Samples for physical-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was reported that TF contents near to 680 mg 100 g −1 sample on dry base and TA contents near to 56 mg cyanidin-3-glucoside 100 g −1 sample on dry base for the leaves of Stachys byzantina were observed, which is also a leafy PANC collected at the same site [28]. The TF contents of 1215.90 ± 201.35 mg 100 g −1 sample on dry base and a TA of 117.23 ± 19.32 mg cyanidin-3-glycoside 100 g −1 sample on dry base were previously presented for in natura GBB leaves collected at the same site [16].…”
Section: Seasonmentioning
confidence: 80%
“…It was reported that TF contents near to 680 mg 100 g −1 sample on dry base and TA contents near to 56 mg cyanidin-3-glucoside 100 g −1 sample on dry base for the leaves of Stachys byzantina were observed, which is also a leafy PANC collected at the same site [28]. The TF contents of 1215.90 ± 201.35 mg 100 g −1 sample on dry base and a TA of 117.23 ± 19.32 mg cyanidin-3-glycoside 100 g −1 sample on dry base were previously presented for in natura GBB leaves collected at the same site [16].…”
Section: Seasonmentioning
confidence: 80%